2015
DOI: 10.1007/s11739-015-1306-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical usefulness and safety of an age-adjusted D-dimer cutoff levels to exclude pulmonary embolism: a retrospective analysis

Abstract: Age-adjusted D-dimer (AADD) appears to increase the proportion of patients in whom pulmonary embolism (PE) can safely be excluded compared with conventional D-dimer (CDD), according to a limited number of studies. The aim if this study was to assess whether the use of an AADD might safely increase the clinical usefulness of CDD for the diagnosis of PE in our setting. Three hundred and sixty two consecutive outpatients with clinically suspected PE in whom plasma samples were obtained to measure D-dimer were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…All but one included study used one or more highsensitivity D-dimer assays (eg, VIDAS, Tinaquant, STA-Liatest, Innovance, and D-dimer HS), which generally use a conventional cutoff of FEU at 500 mg/L. [43][44][45][46][47][48][49][50][51] One study used the HemosIL D-dimer assay, which reported results in DDU that are equivalent to approximately half of an FEU, and the formula for age adjustment was adjusted accordingly (ageÂ5 mg/L). 52 The primary concern when using an age-adjusted D-dimer cutoff is whether increasing the threshold increases the risk of missed PEs.…”
Section: Potential Benefits Of Implementing the Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…All but one included study used one or more highsensitivity D-dimer assays (eg, VIDAS, Tinaquant, STA-Liatest, Innovance, and D-dimer HS), which generally use a conventional cutoff of FEU at 500 mg/L. [43][44][45][46][47][48][49][50][51] One study used the HemosIL D-dimer assay, which reported results in DDU that are equivalent to approximately half of an FEU, and the formula for age adjustment was adjusted accordingly (ageÂ5 mg/L). 52 The primary concern when using an age-adjusted D-dimer cutoff is whether increasing the threshold increases the risk of missed PEs.…”
Section: Potential Benefits Of Implementing the Recommendationsmentioning
confidence: 99%
“…Safety of the Age-Adjusted D-dimer Strategy ( Table 2) Overall, the 3 Class II studies [43][44][45] found that the miss rate of the age-adjusted D-dimer was similar to a conventional D-dimer cutoff, and that the sensitivities were similar. The prospective study by Righini et al 43 took place at multiple centers in Europe and included 3,324 ED patients with a 19% overall prevalence of PE; 87% were at nonhigh risk, and if the D-dimer result was negative, these patients were discharged without additional testing and without anticoagulation.…”
Section: Potential Benefits Of Implementing the Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing body of evidence that age-adjusted ddimer cut-offs have acceptable sensitivity for PE and that their use could avoid a significant proportion of CTPA which carry the risk of adverse effects for patients (such as contrast reaction and contrast nephropathy), often cause inconvenience to patients in terms of an extended ED stay and contribute to reduced ED patient flow by requiring an extended ED stay. 2,5,[7][8][9][10][13][14][15][16] Age-adjusted d-dimer cut-offs are intended to be used in conjunction with a clinical risk score to identify a group of patients in whom PE is unlikely and therefore further imaging can be avoided. There are sparse data comparing the performance of age-adjusted d-dimer cut-offs with the various risk scores in common use.…”
Section: Discussionmentioning
confidence: 99%
“…6 There is good evidence that 'normal' d-dimer concentrations physiologically increase with age leading to a lower specificity for PE and more false positives in older patients. 4,[7][8][9][10] In fact, d-dimer testing is able to rule out PE in 60% of patients aged <40 years but only 5% for patients aged >80 years. 9,10 This results in an increased number of potentially unnecessary and expensive advanced imaging tests in older patients who are also at increased risk of adverse clinical outcomes, such as contrast-induced nephropathy.…”
mentioning
confidence: 99%